Virtual determination of displacements in bell towers of historic buildings subjected to seismic actions and subsidence, using shell elements, linear and modified linear dynamic analysis. Case study: Templo de la Santa Veracruz. - Torres Montes de Oca, Carlos Alberto; Rosas Valencia, José Eduardo (Revista ALCONPAT, 2025)
The objective of this work is to analyze the behavior of the bell towers of a historical temple built with irregular masonry, it is analyzed by means of a finite element model of shell types and turning blocks. The results showed a coherent relationship of the behavior with respect to section changes. Differential subsidence drastically increased the displacements. One limitation was the interruption of access, due to intervention activities in the building. The uniqueness of this work is based on the graphic superposition of the displacements calculated for different combinations of isolated and combined actions. In conclusion, the displacements obtained with time signals are less critical than those determined with response spectrum.